The Effect of Exercise Mobilization on Independence in Daily Activities in Stroke Patients - Prasetya, Arif Bagus; Kristi, Priska Dyana; Pribadi, Agus (Indonesian Conditioning Coaches, 2025)
Long-term functional impairment following a stroke often impairs a patient's ability to do Activities of Daily Living (ADLs). In the acute and chronic stages of stroke, exercise mobilization has been widely advised as a rehabilitation technique to maximize motor recovery and avoid problems connected to immobility. The purpose of this review of the literature is to examine the data pertaining to the efficacy of exercise-based mobilization therapies in enhancing ADL independence in stroke patients. Articles with an emphasis on original research published in authorized or indexed national and international journals between 2015 and 2025 were gathered from the PubMed and Google Scholar databases. A few studies looked at mobilization exercise regimens that were started under expert supervision, including sitting, standing, transfer training, progressive gait exercise, and active or passive range of motion (ROM). Exercise mobilization significantly improves patient independence, as evidenced by higher Barthel Index values, improved mobility performance, and decreased reliance on self-care activities, according to the evaluated evidence. Early organized mobilization was also linked to shorter hospital stays, less problems such muscular weakness and joint stiffness, and better overall rehabilitation results. Excessive mobilization in unstable patients should be avoided, nevertheless, as differences in stroke severity, intervention timing, and training intensity may affect individual therapy outcomes. To sum up, exercise mobilization is a crucial and successful part of stroke rehabilitation that helps restore functional ability and boost independence in ADL. To maximize healing and improve quality of life after a stroke, a progressive exercise program administered early and safely by trained rehabilitation professionals is advised.